Osteoclast-specific marker nuclear factor of activated T-cells, cytoplasmic, calcineurin-dependent 1 expression in stage III giant cell tumor of the bone - Jusoh, Mohd Hanifah (2018)
Introduction: Osteoclastic bone resorption and osteolysis with tendency for local recurrence and pulmonary metastases are a common complication of stage III Campanacci giant cell tumour of the bone (GCTB). Studies have shown RANKL highly stimulates osteoclastogenesis through nuclear factor of activated T-cells, cytoplasmic, calcineurin-dependent 1 (NFATc1), which regulates a number of osteoclast-specific genes. Osteoclastogenesis is retarded in NFATc1 suppression and knock-out embryonic stem cells in vitro. To our knowledge, the regulation of NFATc1 in osteoclastic resorption in GCTB has not been studied in stage III GCTB. It is important to fully understand the osteoclast-associated GCTB pathogenesis to identify a new therapeutic approach by targeting NFATc1 in GCTB treatment. We analyzed NFATc1 expression immuno-histochemistry of 31 consecutive cases of stage III giant cell tumour of the bone to determine the clinico-pathological correlation. Methodology: This observational cross-sectional study evaluated the immunohistochemical staining for NFATc1 expression in 31 consecutive cases of stage III Campanacci giant cell tumour of bone (GCTB) operated and treated at Hospital Universiti Sains Malaysia from January 2004 to December 2017. Expression of NFATc1 was assessed by immunohistochemical staining in all representative archive tumour sections from each patient. Serial sections of 5 m was cut and underwent immuno-histochemical staining. NFATc1 expression over nuclear area of tumor cells was examined using immunohistochemistry. Immunostainings were evaluated in three randomly chosen microscopic fields using a standard light microscope at 40 x 100 magnification by two-blinded independent observers. Positivity for NFATc1 expression was assessed according to percentage of 1000 background cells using an image analysis software (Olympus – U-RFL-T Cell F). The average score from three selected field was taken for statistical analysis using SPSS version 25.0. Statistical analysis was determined using independent t-test for different group and considered statistically significant when p values were less than 0.05. Results: The mean value of NFATc1 expression obtained as a percentage of 1000 background cells was 0.81 with standard deviation of 1.48. The range was between 0.0 to 6.33 with a median of 0.07. Comparison of NFATc1 expression showed higher percentage in recurrence group with mean of 1.01 (SD 0.68) compared to non-recurrence group with the mean of 0.79 (SD 1.55). The mean difference was 0.22 (-1.06, 1.51). This difference was statistically not significant with p > 0.005. A comparison of NFATc1 expression showed higher mean value in lung metastases group which was 2.01 (SD 2.49) compared to 0.58 (SD 1.13) in non-lung metastases group. The mean difference between the two groups were 1.43 (-1.63, 4.49) which is statistically not significant with the p value > 0.005. Conclusions: This study shows not all 31 cases with aggressive GCTB stage III were positively stained with NFATc1 antibody showing the possibility osteoclast may have not been the main cells responsible in the bone destruction in GCTB condition. The mean value of NFATc1 expression was found to be statistically not significant when tested against the risk of pulmonary metastases and recurrence disease, making it not a useful marker to predict the risk of recurrence and pulmonary metastases in aggressive type of GCTB. This study suggested that there must be further research to be carried out to understand other different pathways of bone resorption and osteolysis in GCTB